College Ready at a Cost: Underrepresented Students Overwhelmed, Scared, Increasingly Stressed, and Coping. Issue 5 (June 2020) - Martinez, Melissa A.; Lewis, Katherine; Marquez, Jocabed
As the push and expectation to attend college continues to increase, making the process of getting into college more competitive than ever before, there is a need to interrogate whether and how efforts to create a college-going culture and increase college readiness among students, particularly those from historically marginalized backgrounds, might have an adverse impact on students. This study illuminates 59 students' voices who participated in a multisite descriptive case study examining the strong college-going culture and college readiness efforts at three racially and economically diverse urban public high schools in different regions of Texas. Although students revealed positive aspects of their schools' efforts, this study focuses on some of the negative, unintended consequences related to how students felt and coped with being overwhelmed, scared, and increasingly stressed as a result of the narrow focus on college readiness. Such findings must be considered by scholars, policymakers, and practitioners alike.